2021
DOI: 10.2991/aebmr.k.210416.038
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transformational Leadership in Moderating Job Satisfaction and Intrinsic Motivation on Teachers’ Task Performance

Abstract: The development of education has several important points to be developed. One of them is through teachers' performance. Teachers' role becomes important in generating high quality and competitive graduates. Quantitative method with multiple regression analysis technique was used to observe the influence of work satisfaction and intrinsic motivation towards teachers' performance which was moderated by transformational leadership. The sample consisted of 149 Vocational High School teachers in Pemalang Regency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(38 reference statements)
1
3
1
1
Order By: Relevance
“…Contrary to the conclusions of this study, a certain study found that work motivation had a positive and significant impact on employee performance (Bawono & Setyadi, 2020). Another research showed a strong impact of intrinsic motivation on instructors' performance (Fauzan et al, 2021;Mkubwa & Lyimo, 2019).…”
Section: Effect Of Motivation On Employee Performancecontrasting
confidence: 82%
“…Contrary to the conclusions of this study, a certain study found that work motivation had a positive and significant impact on employee performance (Bawono & Setyadi, 2020). Another research showed a strong impact of intrinsic motivation on instructors' performance (Fauzan et al, 2021;Mkubwa & Lyimo, 2019).…”
Section: Effect Of Motivation On Employee Performancecontrasting
confidence: 82%
“…Mansor et al (2021) exploran cómo la gestión directiva impacta en la seguridad y el desempeño de los docentes, resaltando su rol positivo y significativo. Fauzan et al (2021) destacan la importancia de los docentes en promover competencias, satisfacción laboral y motivación, señalando al LT como un factor crucial en la gestión de prácticas educativas. Bellibaş et al (2021) indican que los directores con un enfoque de LT mejoran el rendimiento estudiantil y responden efectivamente a las demandas de reformas educativas.…”
Section: Situación Problemáticaunclassified
“…The data show that the coefficient of motivation as a mediator is 0.428, and the coefficient of motivation as a predictor of teacher performance is 0.634. Despite the lower level of motivation as a mediator, it has been demonstrated that motivation can have a long-term impact on teacher performance (Azizah & Wahidin, 2022;Fauzan et al, 2021). Motivation, as a mediating variable, can establish a strong relationship with the dependent variable, namely teacher performance.…”
Section: The Influence Of Transformational Principal's Leadership On ...mentioning
confidence: 99%
“…Finally, the job motivation of educators has a significant indirect impact on their success as leaders of a transformational concept. These assumptions are backed by the following (Achmad Kurniadi et al, 2017;Ali, 2022;Anggraini et al, 2023;Azizah & Wahidin, 2022;Fauzan et al, 2021;Pratiwi et al, 2023;Rahayu et al, 2019;Rachman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%